The writing-rich high school classroom engaging students in the writing workshop - Berne, Jennifer (Guilford Press, 2009)
Gives teachers everything they need to set up and manage a successful writing workshop in a high school classroom. After introducing the workshop's fundamental principles and methods, the book explains how to guide students through the entire writing process, from planning and drafting to revising, giving and receiving feedback, editing, and publishing their work. Guidelines for valid, reliable assessment and evaluation of student work are included. --from publisher description
Includes bibliographical references (p. 159-162) and index
Keywords: Englisch; English language -- Composition and exercises -- Study and teaching (Secondary); English language -- Rhetoric -- Study and teaching (Secondary); High school; Unterricht; USA